Collaboration of Progressive Web App (PWA) And Firebase Cloud Messaging (FCM) for Optimal Performance Mailing Software - Dwi Purnomo Putro; Adhika Pramita Widyassari; Dea Salsabilla (International Conference On Digital Advanced Tourism Management And Technology, 2023)
The problem of correspondence cannot be separated from the ease, accuracy and speed of the processing process. In research from Riswandi Ishak and H. Trizaka, they proposed report management software as well as notification of disposition and monitoring of correspondence as a solution to correspondence problems. However, there are shortcomings in the notification process for the disposition of correspondence, which requires the software to be actively open. In research, P. Dwi proposed a notification solution with Firebase Cloud Messaging (FCM), so that it can send notifications as long as the browser is active and connected to the internet, even without opening the software. There is a problem currently when the software becomes unstable when the internet connection is bad or offline. Progressive Web Apps (PWA) offers the concept of web-based application development by implementing browser technology such as service workers and app manifests. PWA is capable of displaying pages offline but cannot save, change, or delete data in the database. The test results of this research used Lighthouse and showed an average score of 100 on the PWA criteria, 85 on the performance criteria, 97 on the accessibility criteria, and 100 on the best practices criteria. Additional results obtained by implementing PWA mean page loading times are 26.6% faster with cache and service workers. The PWA and FCM concepts provide the best experience in using Mailing Software even with minimal internet connection or offline. This strategy was chosen to still get a fast response when running the mail processing software.